LOCAL GEOLOGY AND SITE CLASS ASSESSMENT BASED ON MICROTREMOR DATA IN NORTH LOMBOK - Minardi, Suhayat; Aprianti, Nirmala; Solikhin, Akhmad (Universitas Mataram, 2021)
Lombok Island is an active seismic area in Indonesia potentially hit by an earthquake due to located between two earthquake generators from the south and the North. Several large earthquakes rocked Lombok, an earthquake with a magnitude of 6.4 on July 29, 2018, and 7.0 on August 5, 2018. This study aims to determine the characteristics of the local site effect based on the dominant frequency value ( ), soil amplification ( ), sediment layer thickness (d), , dominant period (T0), and seismic vulnerability index ( ) and to comprehend the soil class (site class) based on the thickness of the sediment layer (d), and in the North Lombok region. The data used is secondary data from microtremor signal recordings in North Lombok Regency in 2018. Data processing used Geopsy software, and microtremor data were analyzed using the HVSR method. From processing the HVSR data, the dominant frequency value about (0.8 - 18) Hz, amplification value (1.7 – 9.7), dominant period value (0.05 – 1.2) seconds, seismic vulnerability index value (0.4 – 71) , and the value of in the study area (20.05 – 287.04) m/s. Based on microtremor analysis, the local site effect indicates that alluvium rocks caused stronger earthquake vibrations and more damage. Whereas the Kalibabak and Lekopiko formations caused fewer earthquake vibrations and less wear. Based on the dominant period and , area study classify as Site Class IV class E and Site Class III class D Copyright © 2021 IPR. All rights reserved.